Realización de bloqueos de nervio periférico (2011)
Background. Technological advances and the development of several new techniques have helped expand the use of peripheral nerve blocks in different situations. This paper is designed to review several issues related with the tecniques to perform peripheral nerve blocks. Methods. The literature search and selection was done in PubMed, Cochrane, Scielo, LILACS; it was expanded on the basis of the references found in texts reviewed by the author; the search was done using the MeSH terms included as keywords. Results. Physiology of neural conduction, functioning of the peripheral nerve stimulator, anatomy of the several neural structures, drugs, and techniques are showed.